Changes in Bacterial Resistance Patterns of Pediatric Urinary Tract Infections and Rationale for Empirical Antibiotic Therapy - (:unkn) unknown (My University, 2017)
0

Background: The causative agent spectrum and resistance patterns of urinary tract infections in children are affected by many factors. Aims: To demonstrate antibiotic resistance in urinary tract infections and changing ratio in antibiotic resistance by years. Study Design: Retrospective cross-sectional study. Methods: We analysed antibiotic resistance patterns of isolated Gram (-) bacteria during the years 2011-2014 (study period 2) in children with urinary tract infections. We compared these findings with data collected in the same centre in 2001-2003 (study period 1). Results: Four hundred and sixty-five uncomplicated community-acquired Gram (-) urinary tract infections were analysed from 2001-2003 and 400 from 2011- 2014. Sixty-one percent of patients were female (1.5 girls : 1 boy). The mean age of children included in the study was 3 years and 9 months. Escherichia coli was the predominant bacteria isolated during both periods of the study (60% in study period 1 and 73% in study period 2). Bacteria other than E. coli demonstrated a higher level of resistance to all of the antimicrobials except trimethoprim-sulfamethoxazole than E. coli bacteria during the years 2011-2014. In our study, we found increasing resistance trends of urinary pathogens for cefixime (from 1% to 15%, p<0.05), amikacin (from 0% to 4%, p<0.05) and ciprofloxacin (from 0% to 3%, p<0.05) between the two periods. Urinary pathogens showed a decreasing trend for nitrofurantoin (from 17% to 7%, p=0.0001). No significant trends were detected for ampicillin (from 69% to 71%), amoxicillinclavulanate (from 44% to 43%), cefazolin (from 39% to 32%), trimethoprim-sulfamethoxazole (from 32% to 31%), cefuroxime (from 21% to 18%) and ceftriaxone (from 10% to 14%) between the two periods (p>0.05). Conclusion: In childhood urinary tract infections, antibiotic resistance should be evaluated periodically and empiric antimicrobial therapy should be decided according to antibiotic sensitivity results.
Keywords: Cerrahi